ФИЗИЧЕСКАЯ КУЛЬТУРА КАК ФАКТОР ВАЛЕОЛОГИЧЕСКОГО И ЭКОЛОГИЧЕСКОГО ВОСПИТАНИЯ СТУДЕНТОВ - Abdukarimov, Nurmaxan (Физическое воспитание, спорт и здоровье, 2021)
In this article, the main categories and concepts that allow to present the ecological education of students in the perspective ofphysical culture of'the individual are defined. The functions examined by its allow the student to master various technologies of ecoTogicaT education and'physical education of the person, which ensure the formation of ecological consciousness and ecological culture. Among these functions are: information, development, orientation, mobilization, constructive, communicative, organizational and research. All these functions are closely related to each other in the integral structure of a specialist's personality and can form the basis of his professional activity in relation to environmental education and human education. The priority of human life and health as a fundamental principle of the state policy of the Republic of Kazakhstan in the field of education is fixed in the Law of the Republic of Kazakhstan "On Education ”.